Association between Body Mass Index with Sugar-Sweetened and Dairy Beverages Consumption in Children from the Mexico–USA Border - Gómez Miranda, Luis Mario (2022)
The consumption of sugar-sweetened beverages has been associated with the onset of cardiometabolic diseases. The aim of this study was to describe consumption patterns of sugar-sweetened and dairy beverages and to evaluate their correlation with the body mass index in children residing at the Mexico–USA border. A total of 722 (370 girls, 352 boys) elementary school children aged 9 to 12 years from Tijuana, Mexico, participated in the study. Anthropometric measures were recorded, and a beverage intake questionnaire was completed by the children’s parents. Significant age by sex interactions were found on body mass index Z-scores (p < 0.01). Boys showed higher sugar intake (p < 0.05) and total relative energy consumption from sugar (p < 0.05) than girls. The energy consumption from sugar-sweetened and dairy beverages was similar between sexes (p > 0.05). Sugar intake from beverages was higher than the limit recommended by the World Health Organization in boys (66%) and girls (44%). A high frequency of consumption of sugar-sweetened beverages and similar intake of dairy beverages were found in children from the Mexico–USA border. The high consumption of sugar exceeds international recommendations and should be carefully monitored.